Integrating Professional Teachers in The Transition of The New Habits Through Professional Teacher Competency Training Karawang District - Isti Aisah; Hinggil Permana (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article aims to train existing teachers at Karawang Regency to become professional teachers during the transition from the pre-new habit stage. In addition to teacher training, this study also aims to identify and determine the level of competence of all teachers on teacher competence. The audience of this dedication are teachers and prospective teachers in Karawang. The methodology used in this service starts with webinars and workshops which are held online through the zoom feature with discussions and questions and answers as well as assignments to display lesson plans or teaching materials that have been used in the learning process during the pandemic. During this study, subjects were asked to take a test and post-test. As a result of this activity, the capacity of professional teachers in the Karawang Regency increased significantly.